Factors Influencing Consumers’ Attitude & Perception towards E-shopping in NCR - Saxena, Dr. Gaurav (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The daily advancing usage of Internet in India helps facilitate growing prospects for shopping online. Online shopping is an advancing sphere of technology. The explosion of online shopping has provided ground for comprehensive research targeted at luring and engaging customers from both the technology-oriented and consumer’s view. Behaviour of consumer is regarded as an applied discipline since mostly decisions are considerably effected by human behaviour or anticipated actions. Most companies today employ the Internet as a means to cut marketing costs, consequently lowering the cost of their services or products with a view of remaining in the lead in a greatly competitive market. Additionally companies deploy the Internet to transfer, communicate and circulate information, to market a product, to obtain feedback as well as to make satisfaction surveys with the consumers. The consumer employs the Internet to purchase a product online, as well as to compare rates, features of a product and after sale service facilities provided after buying the product from a specific website. The current work aims at exploring possible dependent and independent variables that affect customer’s attitude towards E-shopping behavior in NCR. The work is based on a pragmatic research study.